(untitled) (Marketing Journal, 2025)
This article explores the evaluation of the utilization level of industrial enterprisesʼ production capacity. Using the case of “SAM ANTEP GILAM,” the study analyzes production volumes for 2023 –2024, product quality, equipment efficiency, and production rhythm. The proposed methodological approach allows determining the actual state of production potential based on seasonal dynamics and variability coefficients of production indicators.